2013
DOI: 10.1177/156482651303400408
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Insufficiency in a Sunshine-Sufficient Area: Southern Ethiopia

Abstract: Vitamin D insufficiency is a serious problem in the study population, and living near the Equator does not assure adequate vitamin D status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 24 publications
0
13
3
Order By: Relevance
“…[32,33] Ethiopia is located in east Africa close to the equator (3 degree N to 14.8 degree latitude) and there is abundant sunshine to form vitamin D all year round. [34] This study was conducted in Addis Ababa, the capital city of Ethiopia, located at latitude 9 degree N. In the present study, we found no significant influence of seasonal variation (rainy versus dry seasons) on plasma 25 (OH)D 3 concentrations. Our finding is consistent with previous findings from countries located near the equator.…”
Section: Discussioncontrasting
confidence: 43%
“…[32,33] Ethiopia is located in east Africa close to the equator (3 degree N to 14.8 degree latitude) and there is abundant sunshine to form vitamin D all year round. [34] This study was conducted in Addis Ababa, the capital city of Ethiopia, located at latitude 9 degree N. In the present study, we found no significant influence of seasonal variation (rainy versus dry seasons) on plasma 25 (OH)D 3 concentrations. Our finding is consistent with previous findings from countries located near the equator.…”
Section: Discussioncontrasting
confidence: 43%
“…It would be interesting to determine whether lower VD status would predict development of CM. Although individuals in tropical malaria regions may not suffer from low sunlight exposure, VD deficiency is still prevalent in tropical climates despite high amounts of sunlight (4143). Vitamin D production in the skin following UV exposure is significantly less in dark skin and dietary sources for vitamin D is uncommon in most parts of the world.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that vitamin D deficiency is prevalent among Ethiopian schoolchildren both in urban and rural settings accounting for 61.8% and 21.2%, respectively [ 25 ]. Other studies conducted on pregnant women and women of reproductive age group also showed that vitamin D deficiency is prevalent in Ethiopia [ 26 , 27 , 28 ]. There have been a few studies examining the prevalence of overweight and/or obesity and its associated risk factors among schoolchildren in different parts of Ethiopia [ 29 , 30 , 31 , 32 ]; however, none looked at whether vitamin D deficiency was associated with overweight and/or obesity among schoolchildren.…”
Section: Introductionmentioning
confidence: 94%